Smart Parking System Using Fuzzy Logic Controller for Alien Cities - Saqlain, Muhammad; Saeed, Muhammad; Saeed, Muhammad Haris (International Journal of Mathematical Research, 2020)
Traffic is regarded as one of the biggest issues in cities especially in metropolitan areas with high population density. It is the cause of wastage of precious resources that include fuel, money, and most importantly time. One of the reasons for traffic jams is the people finding an appropriate place to park. To address the issue, various techniques have been implemented by different traffic management authorities, and systems of modern cars have been integrated with smart parking solutions. The fuzzy logic controller is regarded as an Artificial Intelligence product that may be used to alleviate the problem. Four linguistic inputs are used in the paper such that parking car unit, distance, number of traffic signals, and parking area to provide one output that is time. This Fuzzy Logic Controller will be useful for the drivers to locate the shortest track among other tracks in the least amount of time. Moreover, the issue of finding an appropriate parking spot can be solved.